Formulación de un plan estratégico para mejorar el posicionamiento de la Academia Pre universitaria Torrealva de la ciudad de Huamachuco. - Pantoja Quiroz, José David (2013)
This thesis aims to develop a strategic plan to improve the positioning of Pre-University Academy Torrealva Huamachuco city, to this end we used a type of non-experimental research, transactional. There were 13 questions which were put at random for the survey of the schools of the city of Huamachuco, to set your preferences and remembrance of that Torrealva Preuniversitaria Academy. In further development were used as data collection techniques: observations, interviews, surveys. One of the results obtained was that the Academy has no Torrealva Preuniversitaria most recall by students in the city of Huamachuco. It was noted that in the results is the need to develop a strategic plan to improve the positioning of Pre-University Academy. As a result of this thesis is concluded: Strategic Plan for Pre-University Academy Torrealva be implemented because it improves its position in the city of Huamachuco also helps to survive in this competitive industry, because the battle is fought in the minds of consumers.